Difference and Necessity in Identity and Control - Emily Erikson (Sociologica)
Harrison White introduced numerous important and generative theoretical insights in his large body of work. In this piece, I focus on describing the impact and implications of two central contributions made in Identity and Control (1992 & 2008), which are also developed in other writings. The first is an articulation of the role of difference, decoupling, and disjuncture in producing meaning. The second is a revelation that certain social processes and theoretical concepts that have been conceived and analyzed as separate are reciprocally linked in ways that have important repercussions for individual behavior and macro-social outcomes.